Características produtivas da população melhorada EGLRuzi#01 e da cultivar Kennedy de Brachiaria ruziziensis sob pastejo - Delprete, Sâmila Esteves_x000D_ . (2018)
The objective was to evaluate productive characteristics under grazing of an improved population of Brachiaria ruziziensis, called EGLRuzi#01, comparing it with the Kennedy commercial cultivar, aiming to evaluate the possibility of launching EGLRuzi#01 as a new forage cultivar. The experiment was implemented in the Experimental Field José Henrique Bruschi (CEJHB) of Embrapa Gado de Leite, in Coronel Pacheco, Minas Gerais State, Brazil. An improved population of B. ruziziensis (EGLRuzi#01) obtained in the third cycle of intrapopulational recurrent selection of the Embrapa Gado de Leite forage breeding program and Kennedy comercial cultivar as a control was evaluated. The variables evaluated were: entrance height; soil cover; tiller population density; leaf percentage, stem and dead material; leaf:stem ratio; pre-grazing forage mass; exit height and post-pastage forage mass. The experimental design was a randomized block design, with two treatments (improved population EGLRuzi#01 and Kennedy cultivar), two blocks and five sub-blocks for the first period and twelve sub-blocks for the second period. Each sub-block was composed of the evaluation dates. The data were submitted to variance analysis (P<0.05) using the SAS MIXED procedure and the maximum likelihood method for estimation of variance components, considering fixed treatment effect and random effects of block and sub-block. There was no significant difference (P<0.05) regarding the entrance height of the animals in the pickets, however, there was a significant difference (P<0.05) for exit height. The exit heights for the EGLRuzi#01 improved population were above the predetermined of 30 cm for the first period and 25 cm for the second. This fact resulted in a lower leaf percentage and higher dead material in the second period (P<0.05). For the variables soil cover, leaf:stem ratio, pre-grazing ans post-grazing forage mass there was no significant difference (P<0.05). There was significant difference (P<0.05) for the tiller population density in the first period, in which the EGLRuzi#01 improved population presented higher value, with 27.90% more tillers per m² in relation to the Kennedy cultivar, a feature that is directly related to pasture perenniality and is related to pasture productivity, which makes interesting the higher tillering characteristic of EGLRuzi#01. Thus, the improved population of B. ruziziensis (EGLRuzi#01) presents superior productive characteristics to the cultivar Kennedy, like the greater tiller population density, that makes it promising to be launched like new commercial cultivar.